Improving safety in organ recovery transportation: Report from the ASTS/UNOS/AST/AOPO transportation safety summit. Issue 8 (17th May 2020) - Axelrod, David A.; Shah, Shimul; Guarrera, James; Shepard, Brian; Scalea, Joseph; Cooper, Mathew; Kandaswamy, Raja
Abstract : Despite the passage of a decade since the tragic loss of an organ recovery team from the University of Michigan, there are currently no national standards governing air and ground transportation of organ recovery personnel. Consequently, the American Society of Transplant Surgeons, the Association of Organ Procurement Organizations, and the United Network for Organ Sharing jointly convened a transportation summit to review and update recommendations for national transportation standards. Expanded air transport quality assurance protocols, including a requirement for two engine turbine‐powered aircraft piloted by two qualified pilots certified through onsite inspections was recommended. Ground transportation providers must ensure adequate safety restraints are available, ambulance avoided if possible, and the use of lights and sirens minimized. Finally, adequate insurance coverage for all team members, including trainees should be provided and should not rely on carrier liability insurance policies. The summit participants have committed the support of their organizations to promote and enact these regulations nationally. Abstract : The authors present consensus recommendations to improve the safety of organ recovery team transportation developed following a national summit sponsored by ASTS, AST, UNOS, and AOPO.